Proposed Perceptions to address reading impairment of Middle School Students from the point of view of their Teachers in Government Schools in the State of Kuwait - Aldhafeeri, Bandar Manshed Mohammad (Journal of Educational and Psychological Sciences, 2021)
The aim of the research is to identify the proposed perceptions to address poor reading among middle school students from the point of view of their teachers and teachers in public schools in Kuwait, and the research sample consisted of (350) teachers, selected in the random class way from middle school teachers in The 2, 512 public education schools in Mubarak al- Kabir governorate (Kuwait) were adopted, and the analytical descriptive curriculum was adopted, and the questionnaire was adopted as a data collection tool consisting of (32) paragraphs spread over three integrated fields as follows: Proposed perceptions to address poor reading related to the role )family and teacher, technical guidance and school curriculum, school and major educational institution).The research resulted in a series of results, the most important of which is that the degree of appreciation of middle school teachers for the proposed perceptions to address poor reading among middle school students in all its integrated areas came to a large extent, the most important of which is the provision of a scientific and cultural stock among the teacher qualifies him to address the reading weakness of students, take into account the family's various problems and stand with him to overcome them, provide modern educational and technological means in the school, provide the major educational institution for all ways to address the problems of students, especially reading weakness, monitor guidance Technical commitment of teachers to the treatment plans provided to students, in addition to the existence of statistically significant differences between the responses of the members of the study sample towards the proposed perceptions to address poor reading in middle school students from the point of view of their teachers and teachers in public schools in Kuwait at all fields and the tool as a whole due to the sex change and the differences came in favor of male teachers.In the light of the results the research made a number of recommendations, the most important of which Taking into account the importance of the diagnostic calendar for students at the beginning of the year and semester, and educating teachers and following them up by their supervisors through regular visits to them during the academic year to identify the weaknesses and strengths of each student, and qualify and prepare Arabic teachers through training courses on addressing poor reading among students .
Keywords: Perceptions; treatment of poor reading; middle school students; teachers of public schools; State of Kuwait